Production of TGF-alpha and TGF-beta by cultured keratinocytes, skin and oral squamous cell carcinomas--potential autocrine regulation of normal and malignant epithelial cell proliferation. - Partridge, M; Green, MR; Langdon, J; Feldmann, M (1989)
Transforming growth factors have a wide range of biological activities related to cell proliferation and differentiation. In general TGF-alpha promotes cell proliferation while TGF-beta may stimulate or inhibit proliferation depending on the cell type and growth factor environment. Cultured human keratinocytes, skin and oral squamous cell carcinomas were analysed for the presence of transcripts and protein for the transforming growth factors alpha and beta. Both growth factors were detected in cultured keratinocytes (which have receptors for and respond to both ligands), and in medium conditioned by these cells. Additionally transcripts for TGF-alpha were found preferentially in the basal, proliferative compartment of cultured keratinocytes. Similarly both growth factors were detected in oral squamous cell carcinomas and a highly significant inverse correlation was found between the levels of TGF-alpha and the epidermal growth factor receptor in these tumours. The data for TGF-alpha are consistent with the existence of an autocrine growth control loop influencing cell proliferation in both a normal cell type and malignant epithelial tissues, a process that in keratinocytes and responsive squamous cell carcinomas could be modulated by TGF-beta.